Sosialisasi Belajar Motorik Melalui Permainan Edukatif Engklek Question Pada SD Plus Ditawijaya di Kota Palembang - Taroreh, Bangkit Seandi; Kesumawati, Selvi Atesya; Endrawan, I Bagus; Muslimin,; Melianty, Selvi; Septaliza, Dewi; Al Banna, Muhammad Zikri (TAAWUN, 2023)
This Community Service activity is aimed at socializing motor learning through engklek question educative games at SD Plus Ditawijaya in Palembang City. The implementation of community service activities is divided into three stages, including: 1) planning, 2) implementation and 3) evaluation. The planning stage was carried out to see the condition of SD Plus Ditawijaya in Palembang City, how the students' activities were while participating in teaching and learning activities, besides that it also checked the readiness of the engklek questions educative game as a medium for learning. At the implementation stage the entire community service team became resource persons. This stage is carried out through a series of socialization events. The evaluation stage aims to see the results of increasing the knowledge of teachers and students learning motor skills through engklek question educational games. Retrieval of data through observation using observation guidelines carried out for 2 days. The subjects consisted of physical education teachers and SD Plus Ditawijaya students with a total of 20 people. The result of this community service activity is that there is an increase in knowledge about motor learning through educational games engklek questions by 40% (8 people) including the high category and 60% (12 people) including the medium category. The hope is that the engklek questions educational game will be an alternative choice for teachers in motor learning activities at school.